Building Interactive Communication with Google Classroom - Subandi, S; Choirudin, C; Mahmudi, M; Nizaruddin, N; Hermanita, H (International Journal of Engineering and Technology, 2018)
Google Apps for Education (GAFE) is a technology is provided and designed for college by promoting the use of information technology and collaboration. One of Google Apps for Education products is Google Classroom being a learning media between for Lecturers and Students to build interactive communication. Interactive communication leads to good feedback in the form of educational transformation from learning source to learner. This is what improves the engagement for the students themselves. By the concept of digital classroom, students no longer just sit passively in the classroom, they are interested in themselves to explore the things offered by technology. Building interactive communication among students need a good strategy. Strategy not only serves as a concept map that shows only direction, but is able to demonstrate operational tactics to achieve the established goals. A teacher or lecturer who does not have a good teaching strategy will not be able to create good communication with students. Building interactive communication among students need a good strategy. Strategy not only serves as a concept map that shows only direction, but is able to demonstrate operational tactics to achieve the established goals. A teacher or lecturer who does not have a good teaching strategy will not be able to create good communication with students.Â Â